Inheriting the sins of their fathers: boar life experiences can shape the emotional responses of their offspring - Sabei, Leandro; Parada Sarmiento, Marisol; Bernardino, Thiago; Çakmakçı, Cihan; Farias, Sharacely de Souza; Sato, Denis; Zanella, Márcia Inês Grapeggia; Poletto, Rosangela; Zanella, Adroaldo José (Frontiers in Animal Science, 2023)
Introduction: The welfare of breeding boars are often overlooked, resulting in limited scientific data to foster discussion of the topic. We aimed to investigate the effect of different boar housing conditions on their offspring's emotionality. Methods: Eighteen boars were housed in three different conditions: crates (C; n = 6), pens (P; n = 6), or enriched pens (E; n = 6). Their distributed by semen quality (SQ; high, medium, or low). Three semen pools were used to inseminate 13 gilts housed in outdoor paddocks. At 25 days of age, 138 suckling piglets were subjected to open field (OF), novel object (NO), and elevated plus-maze (EPM) tests. Saliva was collected before and after the OF-NO tests to measure cortisol concentrations. At the end of the experiment, hair samples were collected for DNA paternity tests. Piglets were classified based on their behavioral responses using hierarchical cluster analysis of the principal components extracted from factor analysis of mixed data. The variables were reduced to seven principal components (dimensions, Dims), which explained 73% of the total variation, and were analyzed using linear mixed models. The models included each Dim as a dependent variable, paternal treatment and body weight (BW) as fixed effects, and paternal SQ as a random effect. Kruskal‒Wallis and Wilcoxon rank-sum tests were used to compare the cortisol concentration ratios (before and after the OF-NO tests) between groups. Results: There was an effect of treatment on Dim 3 (EPM; activity/fear), with higher values of C piglets than E piglets (p = 0.047). Although C piglets had significantly higher values than P piglets in Dims 4 (EPM; anxiety; p = 0.029) and 6 (NO; inactivity far from the object/exploration; p < 0.0001), the effect of the paternal treatment × BW interaction was significant in both dimensions (p < 0.05). The cortisol ratio in E piglets was greater than that in P and C piglets (p < 0.05). Discussion and conclusion: Our findings indicate that boar breeding environments affect the stress response and emotionality (anxiety, fear, and exploration) of their offspring.